Weight and head circumference at birth in function of placental paraben load in Belgium: an ENVIRONAGE birth cohort study - Vrijens, Karen; Van Overmeire, Ilse; De Cremer, Koen; Neven, Kristof Y.; Carollo, Riccardo M.; Vleminckx, Christiane; Van Loco, Joris; Nawrot, Tim S. (Environmental health, 2020)
Background Parabens are a group of esters of para-hydroxybenzoic acid utilized as antimicrobial preservatives in many personal care products. Epidemiological studies regarding the adverse effects of parabens on fetuses are limited. The aim of this study was to determine the association between placental paraben exposure and birth outcomes. We assessed paraben concentrations in placental tissue, which potentially gives a better understanding of fetal exposure than the maternal urinary concentrations which are the current golden standard. Methods Placental tissue was collected immediately after birth from 142 mother-child pairs from the ENVIR ON AGE birth cohort. The placental concentrations of four parabens (methyl (MeP), ethyl (EtP), propyl (PrP), and butyl (BuP)) were determined by ultra-performance liquid chromatography coupled with tandem mass-spectrometry. Generalized linear regression models were used to determine the association between paraben exposure levels and birth outcomes. Results The geometric means of placental MeP, EtP, PrP, and BuP were 1.84, 2.16, 1.68 and 0.05 ng/g tissue, respectively. The sum of parabens (∑ parabens, including MeP, EtP and PrP) was negatively associated with birth weight in newborn girls (− 166 g, 95% CI: − 322, − 8.6, p = 0.04) after adjustment for a priori selected covariates. The sum of parabens was negatively associated with head circumference (− 0.6 cm, 95% CI: − 1.1, − 0.2, p = 0.008) and borderline associated with birth length (− 0.6 cm, 95% CI:-1.3, 0.1, p = 0.08). In newborn girls the placental concentration of EtP was negatively associated with head circumference (− 0.6 cm, 95% CI:-1.1, − 0.1, p = 0.01) and borderline significantly associated with birth weight and birth length. Lastly, placental EtP and ∑parabens were negatively associated with placental weight in newborn girls but not in newborn boys (− 45.3 g, 95% CI:-86.2, − 4.4, p = 0.03). Conclusion The negative association between maternal paraben exposure and birth outcomes warrants further research and follow-up over time to determine long term effects of gestational exposure to parabens.